(untitled) (Journal of Solar Energy Research Updates, 2021)
This paper describes the history and evolution of technologies related to the whole electrical system of solar car [1]. The components are the solar cell, maximum power point tracker, boost converter, motor& Inverter and battery. In a solar car, it is difficult to arrange the solar cells on a flat vehicle surface, and solar cells with different incident angles and temperature is different in each cell. This is a problem when many solar cells with different characteristics are connected in series, and the improvement method will be described in detail. Next, we will explain the development of a boost converter using a GaN power device that can improve the overall running efficiency. We will also discuss the technological advances in motors & inverters and batteries over the last 30 years. The evolution of solar cars is largely due to the evolution of semiconductors, including solar cells, and material technologies, but at the same time, we will explain examples of these technologies being first demonstrated in solar car race and then socially implemented